The Effectiveness of ATraining Program To Develop Health and Safety Skills for Kindergarten - Salman, Asmaa Abduljabbar (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to identify the effectiveness of a training program to develop health and safety skills for kindergarten children . To achieve this goal, a number of null hypotheses were developed, which are: 1-  There is no statistically significant difference at the level (0.05) in health and safety skills between the children of the experimental group and the children of the control group in the pre-test . 2-  There is no statistically significant difference at the level (0.05) in health and safety skills between the children of the experimental group and the children of the control group in the post test. 3-  There is no statistically significant difference at the level (0.05) in health and safety skills between the children of the experimental group and the children of the control group in the first post-test and the second post-test. The program was applied to preschool children in Diyala Governorate / Baquba District. The result of the research indicated the effectiveness of the training program that was applied to the children of kindergarten and for the benefit of the experimental group.